Does YouTube Provide Qualified Patient Education Videos About Atrial Fibrillation? - Luo, Chong; Bian, Longrong; Jiang, Lijie; Liang, Weitao; Wu, Zhong (Frontiers in Public Health, 2022)
Objective: Patients are utilizing the Internet as a pathway to acquire conveniently the knowledge of specific diseases which they are concerned. However, there is limited oversight and review mechanisms for the concerns of authenticity on online information. This study aimed to appraise the quality of video-based resources for atrial fibrillation (AF). Methods: Multiple AF-specific keywords were used to perform a systematic YouTube search. Two independent reviewers reviewed through the top 50 results from each keyword search. To record data, the Journal of the American Medical Association Score (JAMA), modified DISCERN score, and the Atrial Fibrillation Specific Score (AFSS), Escore were employed. And the Kruskal-Wallis test was used for intergroup comparisons. Results: A total of 74 videos met inclusion criteria and were finally included in the analysis. In terms of video quality, Poor accounts for 68%, followed by Moderately (19%) and Exceptional (13%). Publishers with a medical background were much less popular (P<.05) than those from non- professional and video quality does not differ from others. Conclusions: Through this study, we found that some of the videos on YouTube that are of real value are not as popular as the low-quality content summited by News agency/ We media publishers and that those with a medical background do not receive as much attention as others. It is important to acknowledge that video platform should establish an auditing mechanism for videos in content and quality, meanwhile publishers should ensure that viewers receive accurate and complete knowledge, while using more concise or accessible images or animations that are tailored to the audience.